2005
DOI: 10.1007/s11916-005-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment in cluster headache: Evidence, rationale, and practice

Abstract: The use of corticosteroids in the treatment of cluster headache (CH) is commonplace and has been a mainstay of clinical practice for this indication for 50 years. The published evidence supporting this practice is weak, with no methodologically rigorous or large-scale controlled trials executed. Nonetheless, the clinical experiences of practitioners and the conclusion of investigators provide a clear signal of benefit from corticosteroid use in CH. The pathophysiologic explanation for this beneficial effect is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…However, these studies have nearly uniformly reported positive treatment effects, and this is consistent with the clinical experiences of most physicians caring for CH patients. [27] Caution has to be exercised in their use because of the potential for serious side-effects. Thus, a tapering course of prednisone or prednisolone for 3 weeks is prudent.…”
Section: Cluster Headachementioning
confidence: 99%
“…However, these studies have nearly uniformly reported positive treatment effects, and this is consistent with the clinical experiences of most physicians caring for CH patients. [27] Caution has to be exercised in their use because of the potential for serious side-effects. Thus, a tapering course of prednisone or prednisolone for 3 weeks is prudent.…”
Section: Cluster Headachementioning
confidence: 99%
“…Moreover, there are no double-blind placebo-controlled studies of corticosteroid efficacy: nonetheless, corticosteroids have been used for rapid CH control for more than 60 years Horton (1952). Oral and intravenous corticosteroids may be beneficial Ashkenazi & Schwedt (2011); Shapiro (2005). For oral administration, daily 40–80 mg prednisolone with gradual reduction over 10 days or longer is recommended Couch & Ziegler (1978).…”
Section: Discussionmentioning
confidence: 99%
“…I know the recently published European guidelines for CH treatment recommend the use of steroids, but I like to stay away from them even short term [28••]. I'm probably one of the few who rarely uses steroids for cluster headache, even for short-term or bridging therapy, even though it's clear they are effective [29].…”
Section: Response To Vignette 5 a Patient With Intractable Ch Dependmentioning
confidence: 99%